Prime power for shipboard high-average power FELs - Lyon, Robert Allen (Monterey, California. Naval Postgraduate School, 2013)
Approved for public release; distribution is unlimited. === High-power free electron lasers (FELs), capable of deployment aboard naval combatants, would place a unique and significant demand upon the ship's electrical distribution system. A shipboard FEL must be power efficient, relatively compact, and present a minimum radiation hazard to nearby personnel. The feasibility of deploying an FEL aboard a ship is analyzed from a power system perspective. To produce 1 MW of laser power, it is determined that 6.6 MW of high-voltage dc power is required to drive the FEL when superconductor accelerator technology is employed and 9 MW is required when conventional room temperature accelerator technology is used. The required prime power electrical distribution is easily compatible with the gas turbine engineering plants of modern surface combatants. This distribution will add 22 tons to the ship's displacement and require 22 m3 of the ship's volume to implement. Simulation results show that the FEL would require an undulator with only 16 periods to produce 1 MW for the electron beam parameters developed during the power analysis. This FEL exhibits a large tolerance to electron beam quality. From a power analysis viewpoint, FELs may become a competitive technology for a prospective naval laser weapon